Role of Conscious Control is in the Dynamics of Vocal Activity of Persons After Stroke with an Agile Eferentnoy Aphasia - Milinchuk, V. (Psychological Prospects Journal, 2018)
The article reflects the results of the study focused on speech rehabilitation of persons after stroke. The author has found that the patients’ conscious control somehow plays a vital role in the correction work. Among other findings are neuropsychological principles that underlie using the potential of conscious control in psychic rehabilitation of the patients under consideration.
Keywords: persons after stroke, rehabilitation period, conscious control, speech rehabilitation, neuropsychological principles